The Analysis of Marketing Mix on Consumer Loyalty: Empirical Study of Customer Satisfaction of Local Product - Sonya Lisabel Malelak; Budi Setiawan; Silvana Maulidah (Garuda Prestasi Nusantara Consulting, 2021)
The purpose of this study is to analyze the effect of marketing mix on local product consumer satisfaction, to analyze the effect of marketing mix on consumer loyalty of local products and to analyze the indirect effect of marketing mix on consumer loyalty. This study used 140 respondents and the data were processed using SEM-WarPLS analysis. The results showed that the marketing mix: variable product, price, place, promotion directly has a positive and significant effect on the variable customer satisfaction. Marketing mix: product, price, promotion variables directly have a positive and significant effect on consumer loyalty. place variable has a positive and insignificant effect on consumer loyalty. The importance of maintaining the quality of smoked beef products is emphasized in this study by paying close attention to the processed ingredients and packaging that are unique, as well as periodic product control. This is done so that the products produced can survive in the market and face competitors, as well as to establish more consistent pricing policies so that prices can be more competitive.